PeakTrace: Routing of hydropeaking waves using multiple hydrographs—A novel approach. (27th April 2022) - Greimel, Franz; Grün, Bettina; Hayes, Daniel S.; Höller, Norbert; Haider, Julia; Zeiringer, Bernhard; Holzapfel, Patrick; Hauer, Christoph; Schmutz, Stefan
Abstract: Hydropeaking is known for its adverse impacts on river ecosystems. However, the implementation of mitigation measures is still largely pending due to conflicting priorities of ecology and economics, which require scenario building to assess trade‐offs. Therefore, widely applicable and standardized tools are needed to analyze hydropeaking hydrology in affected rivers to expedite mitigation efforts. Here, we present a novel empirical approach—PeakTrace—that can (a) detect and follow source‐specific hydropeaking waves in the downstream direction by using multiple hydrographs and (b) describe how to flow metrics of hydropeaking waves change along a river's course. In detail, PeakTrace first identifies associated flow events and then models translation and retention processes between neighboring hydrographs. Finally, the models can be combined to establish a non‐linear hydropower plant‐specific model. We demonstrate the PeakTrace method's usability in 16 Austrian case studies. The results underline the high performance of PeakTrace, describing the longitudinal development of flow metrics with high model accuracy up to 25 km or more. Ecologically‐relevant metrics, such as rate of change or amplitude, decrease with distance from the hydropower outlet regarding down‐ramping events; the same pattern can be observed for up‐ramping events too, except for the rate of change for which an intensity increase may be observed, probably due to slope and the roughness difference between base flow and peak flow. Overall, this paper underlines the usability of PeakTrace as a basis to assess hydropower plant‐specific hydro‐ecological impacts and evaluate hydropeaking mitigation measures, especially by incorporating critical flow thresholds of river biota and life stages.